Des poissons morts, des enquêtes et des rivières différentes - Simon Calla (Développement Durable et Territoires)
Most of the time, pollutions are perceived as « already there » phenomena waiting to be established. On the contrary, this paper explains that pollutions are the result of a qualification process embracing both human and non-human entities involved in a given situation. Starting from the observation of dead fishes in a well-known river – la Loue, this paper analyses the inquiries led by fishermen, scientists and authorities aiming at solving problematic situations. In the search for solutions, the various stakeholders refer to different type of knowledge and to different social worlds in which rivers bear different meaning.